2023
DOI: 10.3390/agronomy13010238
|View full text |Cite
|
Sign up to set email alerts
|

Determining Optimal Levels of Pruning in Hylocereus undatus [(Haw.) Britton and Rose] in Trellis Systems

Abstract: The main objective of this work was to determine the optimum level of pruning in pitaya. In addition, we want to establish the relationship between pruning levels and the intensity of flowering, and between flowering levels and heavy flower bud drop that affects this species. With these aims, two experiments were performed on Hylocereus undatus [(Haw.) Britton and Rose] cultivated in greenhouses and trained in a trellis system. Our results conclude that cane pruning leaving 15 cladodes per meter in a trellis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A study on H. undatus pruning shows that cane pruning induces maximum flowering and produces new shoots as compared to spur, spur–cane combined, and sanitary pruning [ 136 ]. Another study further reported improved yield characteristics of pitaya with cane pruning, leaving 12 and 15 cladodes per meter on a trellis [ 137 ].…”
Section: Agronomy Cultivation Pests and Diseasesmentioning
confidence: 99%
“…A study on H. undatus pruning shows that cane pruning induces maximum flowering and produces new shoots as compared to spur, spur–cane combined, and sanitary pruning [ 136 ]. Another study further reported improved yield characteristics of pitaya with cane pruning, leaving 12 and 15 cladodes per meter on a trellis [ 137 ].…”
Section: Agronomy Cultivation Pests and Diseasesmentioning
confidence: 99%